Controlling Power Abuse in Public Policy Cycle - Hai, Do Phu (VNU Journal of Science: Policy and Management Studies; Vol 35 No 1DO - 10.25073/2588-1116/vnupam.4156, 2019)
Abstract: Studying the control of power abuse in the public policy cycle is a new appropriate approach used in the policy science. It is a dynamic examination of the control of political power abuse, which helps reveal the role of the socio-political actors in the control of power abuse. First, the article analyses the political actors’ role to the public policy cycle. Then, it clarifies the mechanism for controlling power abuse by the core actors in the public policy cycle, namely controlling the power of the Communist Party of Vietnam with the participation of the Fatherland Front and its member organizations in public policy planning, public policy evaluating as well as controlling the State power with its key role in formulating and implementing public policies in Vietnam. Keywords: Power, control of power abuse, public policy cycle.